2016
DOI: 10.1038/srep36181
|View full text |Cite
|
Sign up to set email alerts
|

Real time monitoring of membrane GPCR reconstitution by plasmon waveguide resonance: on the role of lipids

Abstract: G-protein coupled receptors (GPCRs) are important therapeutic targets since more than 40% of the drugs on the market exert their action through these proteins. To decipher the molecular mechanisms of activation and signaling, GPCRs often need to be isolated and reconstituted from a detergent-solubilized state into a well-defined and controllable lipid model system. Several methods exist to reconstitute membrane proteins in lipid systems but usually the reconstitution success is tested at the end of the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 57 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…Therefore, the observed spectral changes can only be attributed to ligand‐induced receptor‐conformational changes. Such scenario has already been observed in previous PWR experiments involving ligand interaction with GPCRs . From PWR experiments, it was possible to determine a binding affinity of 0.8 n m between maraviroc and the CCR5 (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, the observed spectral changes can only be attributed to ligand‐induced receptor‐conformational changes. Such scenario has already been observed in previous PWR experiments involving ligand interaction with GPCRs . From PWR experiments, it was possible to determine a binding affinity of 0.8 n m between maraviroc and the CCR5 (Fig.…”
Section: Resultssupporting
confidence: 70%
“…In view of the fact that some indirect studies, either based on Chol depletion (by β‐cyclodextrin) or Chol reduction by drugs (filipin, nystatin), have indicated a potential role of Chol in CCR5 signaling and HIV infection , we have set to directly investigate Chol impact in the first signaling event, that is ligand binding to the receptor and consequent receptor‐conformational changes. Previous data from our group suggested Chol to have an impact in receptor/ligand affinity; nonetheless, such studies were quite preliminary and performed with and engineered CCR5 thermostable mutant, rather than the wild‐type form . The present work, performed with wild‐type CCR5 produced via two alternative and completely independent sources, P. pastoris and cell‐free expression, simultaneously reveals Chol to significantly impact maraviroc affinity to the receptor with a 20‐ to 30‐fold decrease in affinity when Chol is present in the membrane.…”
Section: Discussionmentioning
confidence: 67%
“…These correspond, respectively, to the long and short axis of lipids and proteins (Fig. 2a ) 28 , 29 . PWR is a well-established method to follow ligand-induced receptor conformational changes 15 , 16 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 95%
“…This technique gives the possibility of following resonance with two types of polarizations, p - and s -polarizations. PWR can be applied both to artificial lipid model systems with reconstituted receptors or to cell fragments 27 34 . In the present study, cell membrane fragments from cells expressing the CXCR3-A and CXCR3-B receptors were immobilized on the PWR sensor which is composed of a prism coated with a silver layer and overcoated with a silica layer.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we used PWR to assess CXCR3-A and CXCR3-B conformational dynamics after agonist stimulation. PWR is a validated method to investigate, besides ligand affinity, receptor dynamics after agonist or antagonist exposure 27 34 . PWR studies revealed that, in addition to differences in affinity, PS373434 also induces different conformational changes depending on the CXCR3 isoforms.…”
Section: Discussionmentioning
confidence: 99%